PENDEKATAN SOSIOLOGI DALAM KAJIAN PENDIDIKAN ISLAM - Daimah Daimah; Setyo Pambudi (Universitas Muhammadiyah Prof Dr Hamka, 2018)
This article analyses the Sociology of Education that refers to the application of sociological knowledge, thinking techniques, and data collection in educational investigations. The sociology of education studies the process of education as social interaction, school as a social group, and as a social institution. Sociological analysis models of education include 4 types of analysis, (1) analysis of functional structural models with characters Emile Durkeim and Talcott Parsons, (2) analysis of conflict models with characters S. Bowles and H. Gintis and Louis Althuser, (3) analysis the critical sociology model with its characters Paulo Freire and Ivan Illich and (4) Analysis of the English and US versions of Micro-level Education. Keywords: Sociology Theory, Islamic Education, Sociological analysis models, the process of education